(untitled) (Iter, 2022)
This paper endeavours to examine truth in Platón in accordance with the uses and significations given in the various contexts o f his dialogues. Thus therefore it is possible to see that truth is related to space, visión, speech and finally, in a significative way, to the Good. This aspect is specially devoloped here, and it is concluded that truth -as considered according to the dialectical method- is the intelligible manifestation o f that Good wherefrom it accomplishes its being.